The Role of Sharia Risk Management, Islamic Investment Ethics, and Riba-Free Financing in the Development of the Halal Industry in Indonesia - Judijanto, Loso; Mokodenseho, Sabil; Birah, Ismail Fahriassin; Mamonto, Anggi; Mokodongan, Gia Lestia (Jurnal Multidisiplin West Science, 2024)
The Halal industry has emerged as a significant economic sector globally, driven by the growing demand for products and services that conform to Islamic principles. In Indonesia, with the world's largest Muslim population, the Halal industry has enormous potential for growth. This study investigates the role of Shariah risk management, Islamic investment ethics, and usury-free financing in shaping the trajectory of the Halal industry in Indonesia. Using quantitative analysis through structural equation modeling (SEM), this study examines the relationship between these financial practices and the development of the Halal industry. Data collected from key stakeholders in the industry revealed significant positive relationships between Shariah risk management, Islamic investment ethics, usury-free financing, and Halal industry development. The findings provide valuable insights for policy makers, investors, and industry stakeholders looking to foster sustainable growth and innovation in the Halal industry in Indonesia.